1997
DOI: 10.1095/biolreprod57.6.1384
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Pregnancy-Associated Glycoproteins are Secreted by Day 100 Ovine Placental Tissue1

Abstract: Pregnancy-associated glycoprotein (PAG)-1 (PAG1) and pregnancy-specific protein B are either identical or closely related antigens released by trophoblast binucleate cells of placentas of cattle. Sheep and other ruminants produce similar products. There is evidence, however, that these antigens, which are related structurally to the pepsinogens and other aspartic proteinases, are not single gene products but members of an extensive family. Here, the sequential use of ammonium sulfate precipitation and Sepharos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
67
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(69 citation statements)
references
References 26 publications
1
67
1
Order By: Relevance
“…This highlighted at an early date the surprising size and diversity of this glycoprotein family in sheep. Xie et al [9] confirmed this diversity when, using a series of chromatographic procedures, they purified four additional molecules from the medium after culture of explants from day-100 ovine placenta. These molecules were named according to their molecular masses: ovPAG 55 , ovPAG 60 , ovPAG 61 , and ovPAG 65 .…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…This highlighted at an early date the surprising size and diversity of this glycoprotein family in sheep. Xie et al [9] confirmed this diversity when, using a series of chromatographic procedures, they purified four additional molecules from the medium after culture of explants from day-100 ovine placenta. These molecules were named according to their molecular masses: ovPAG 55 , ovPAG 60 , ovPAG 61 , and ovPAG 65 .…”
Section: Introductionmentioning
confidence: 92%
“…The stage of pregnancy was assessed by measuring the crown-rump length of the foetuses [15]. As in previous works, the placentae were collected after day 100 [9,10]; in this study the period was focused on days 60 to 100. Total protein (TP) concentrations of all fractions were determined by the Lowry method [16].…”
Section: Extraction and Fractionationmentioning
confidence: 99%
See 1 more Smart Citation
“…Bovine and ovine cDNA encoding PAG-1 have 86% similarity in nucleotide sequences and results in encoded proteins which differ in only 2 amino acids (XIE et al, 1991). There are numerous isoforms of PAGs produced from ovine placenta (e.g., ovPAG-55, 57, 59, 60, 61 and 65), which were identified at random stages of pregnancy and used to develop PAGs-based assays with placental antigens from ewes (XIE et al, 1997;EL AMIRI et al, 2003;EL AMIRI et al, 2004). These studies involving sheep PAGs were based on radioimmunoassay (RIA), a radioactive technique (DE SOUSA et al, 2003;KAREN et al, 2003).…”
Section: O Diagnóstico De Gestação é Uma Ferramenta Importante No Manmentioning
confidence: 99%
“…This feature of the modern/ BNC PAGs has been exploited as the basis for pregnancy diagnosis in cattle and related ruminants. Not surprisingly, the modern PAGs have received the bulk of attention from animal scientists and have been the subject of several biochemical, molecular and functional studies (Del Vecchio et al, 1996;Xie et al, 1997;Green et al, 2000;Hughes et al, 2003;Klisch and Leiser, 2003;Weems et al, 2003;Wooding et al, 2005;Klisch et al, 2008). However, despite such efforts, the functional role of the PAGs remains a mystery.…”
Section: Introductionmentioning
confidence: 99%